Ericoid fungal diversity: Challenges and opportunities for mycorrhizal research. (December 2016) - Leopold, Devin R.
Abstract: Ericoid mycorrhiza occur only within the plant family Ericaceae, yet are globally widespread and contribute to carbon and nutrient cycling in many habitats where harsh conditions limit decomposition and plant nutrient uptake. An increasingly diverse range of fungi are recognized as ericoid symbionts and patterns in the distribution of ericoid taxa are beginning to emerge across scales. However, the true diversity of ericoid mycorrhizal fungi remains unresolved due to limited sampling from some regions and challenges associated with delineating mycorrhizal taxa from the broader fungal community associated with ericoid plants. Interpreting patterns in the diversity and distributions of ericoid mycorrhizal fungi will ultimately require improved understanding of their functional ecology and functional diversity, which is currently limited to a few well studied species. Fortunately, many ericoid taxa are amenable to experimental manipulation and continued ericoid mycorrhizal research promises to improve general understanding of the ecology and evolution of mycorrhizal symbioses.